Prevalence and antimicrobial resistance of canine urinary tract pathogens. (7th December 2013) - Hall, J. L.; Holmes, M. A.; Baines, S. J.
Abstract : This study aims to describe the incidence and risk factors for positive urinary tract culture, the prevalence of urinary tract pathogens in single organism and mixed cultures and changes in their antimicrobial resistance over 10 years. A retrospective review of computer records detailing canine urine samples submitted between August 1999 and September 2009 for culture and sensitivity in a UK tertiary referral hospital is described. 17.5 per cent of 5923 samples (670 of 4530 dogs) were positive cultures. 85.3 per cent of cultures yielded a single isolate. The prevalence of bacterial species differed between mixed and single isolate cultures. Entire and neutered female dogs were more likely to return positive cultures than male dogs (OR=2.5 and 1.5, respectively). Escherichia coli was most commonly isolated (53.9 per cent) and affected female dogs, older dogs and neutered dogs more. There was an increase in the antimicrobial resistance of Enterococcus faecalis and Pseudomonas Aeruginosa, and a decrease in the effectiveness of enrofloxacin, cephalexin and oxytetracycline. The prevalence of urinary bacterial isolates is described for a large group of dogs. Monitoring changes in antimicrobial efficacy and microbial resistance guides the empirical use of antimicrobials for the treatment of urinary tract infection and helps formulate strategic plans to limit drug resistance.